Studien zur Systematik und Faunistik der Gattung Tachyporus Gravenhorst - Teil 7. Alte und neue Tachyporus aus dem Fernen Osten, Sachalin und Japan (Coleoptera: Staphylinidae, Tachyporinae). - Schülke, Michael (Contributions to Entomology = Beiträge zur Entomologie, 1998)
The Tachyporus species of Japan and Sachalin are revised. 16 species are recorded from this region (Japan 11 species, Sachalin 7 species). Lectotypes are designated for the following species Tachyporus celatus Sharp, 1874; Tachyporus oculatus Sharp, 1888 and Tachyporus suavis Sharp, 1888. Three species from Japan (celatoides sp. n. (Honshu), cephalotes sp. n. (Honshu) and japonicus sp. n. (Shikoku and Honshu)), two species from Sakhalin (puetzi sp. n. and wrasei sp. n.) and two species from the Russian Far East (ussuriensis sp. n. (Mt. Olkhovaja) and zerchei sp. n. (Chabarovsky Kray)) are described. Tachyporus manchuricus Bernhauer, 1939 is regarded as a synonym of Tachyporus terminalis Sharp, 1888. Tachyroprus klapperichi Schülke and Tachyporus abdominalis (Fabricius) are new records from Japan. Drawings of the aedeagi and elytral chaetotaxy of the species dealt with in the study are provided, a key of the Tachyporus species of Japan and Sakhalin is presented. The distribution of the species and their origin are discussed.KeywordsColeoptera, Staphylinidae, Tachyporinae, Tachyporus, Species novae, New Synonym, Lectotypes, Palaearctic, Russia, Siberia, Sachalin, Japan.Nomenclatural Actscelatoides Schülke, 1998 (Tachyporus), spec. n.celatus Sharp, 1874 (Tachyporus), Lectotypecephalotes Schülke, 1998 (Tachyporus), spec. n.japonicus Schülke, 1998 (Tachyporus), spec. n.manchuricus Bernhauer, 1938 (Tachyporus), syn. n. of Tachyporus terminalis Sharp, 1888oculatus Sharp, 1888 (Tachyporus), Lectotypepuetzi Schülke, 1998 (Tachyporus), spec. n.suavis Sharp, 1888 (Tachyporus), Lectotypeussuriensis Schülke, 1998 (Tachyporus), spec. n.wrasei Schülke, 1998 (Tachyporus), spec. n.zerchei Schülke, 1998 (Tachyporus), spec. n.